Enhanced dielectric, ferroelectric, energy storage and mechanical energy harvesting performance of ZnO–PVDF composites induced by MWCNTs as an additive third phase. Issue 37 (1st September 2021) - Pratihar, Shewli; Patra, Aniket; Sasmal, Abhishek; Medda, Samar Kumar; Sen, Shrabanee
Abstract : Improvement of dielectric, ferroelectric and piezoelectric properties of PVDF/ZnO composites was achieved after MWCNT addition. Abstract : The present work highlights an attempt of fabricating a nanocomposite by the addition of multi-walled carbon nanotubes (MWCNTs) as a third phase into flexible ZnO–poly(vinylidene fluoride) (ZnO–PVDF) composites. MWCNTs played a very important role in distributing ZnO fillers in the PVDF matrix more homogeneously and increased the connection capability. Enhancement of the piezoelectric phase, dielectric permittivity, ferroelectric polarization, energy storage density and mechanical energy harvesting performance of ZnO–PVDF composites after the addition of MWCNTs was confirmed from the respective characterization studies. The sensing capability was demonstrated by the generation of ∼22 V ac output voltage through the application of human finger tapping on 15 wt% ZnO and a 0.1 wt% MWCNT-loaded PVDF (15PZNT) based composite film. The rectified voltage from the fabricated 15PZNT film was used to charge a 10-μF capacitor up to ∼3 V which was used for the illumination of 30 commercial LEDs. The maximum power density from the film was found to be 21.41 μW cm −2 at 4 MΩ load resistance. The effect of the addition of MWCNTs was also verified by simulation using COMSOL Multiphysics software.